Bioactive compounds from Chinese herbal plants for neurological health: mechanisms, pathways, and functional food applications - Wang Meng; Wang Chao; Zhao Kaiwei; Ma Sijia; Sang Jiajia; Xu Shijie (Frontiers in Nutrition)
Neurological disorders pose significant global public health challenges, with a rising prevalence and complex pathophysiological mechanisms that impose substantial social and economic burdens. Traditional Chinese Medicine (TCM), with its holistic approach and multi-target effects, has gained increasing attention in the treatment of neurological diseases. This review explores bioactive compounds derived from Chinese herbal plants, focusing on their mechanisms of action, underlying pathways, and potential applications in functional food development. The review highlights the neuroprotective properties of flavonoids, alkaloids, polysaccharides, and polyphenols found in key TCM herbs such as Scutellaria baicalensis, Salvia miltiorrhiza, Ligusticum chuanxiong, and Gastrodia elata. These compounds have demonstrated significant anti-inflammatory, antioxidant, and neurogenic effects, making them promising candidates for the prevention and treatment of neurological conditions, including Alzheimer’s disease (AD), Parkinson’s disease (PD), and depression. Furthermore, the synergistic effects of TCM formulations targeting multiple signaling pathways offer advantages over single-target therapies, especially in combating neurodegenerative diseases. The review also discusses the challenges and future directions for integrating these bioactive compounds into functional foods and dietary supplements, aiming to improve neurological health and enhance clinical outcomes. Ultimately, this work aims to provide valuable insights into the potential of TCM-based interventions for promoting neurological well-being and addressing the global burden of neurological disorders.